Relationship of Hypertension Control Factors with Blood Pressure in Hypertension Patients at Pandanwangi Primary Health Care Malang - Devi Rahmaningrum Wardani; Erna Dwi Wahyuni; Lailatun Ni'mah (Critical Medical and Surgical Nursing Journal (CMSNJ), 2021)
Introduction: Hypertension is a common cause of the increase of mortality rate and morbidiety in the community. Complications of hypertension cause approximately 9.4 deaths around the world each year. The purpose of this study is to analyze the relationship of factors controlling hypertension with blood pressure.Methods: This study used a descriptive correlational design with the cross sectional approach. The study population was patients with hypertension in Puskesmas Pandanwangi Malang City. The sample used as many as 96 people based on purposive sampling technique. The instruments used were questionnaire sheets, spyghmomanometer and stethoscope. Analysis using the test Spearman rho test with a significance level of p <0.005.Result: The results showed there are a relationship between knowledge (p = 0.000 and r = 0.778), attitude (p = 0.000 and r = 0.626), diet (p = 0.000 and r = 0.609), physical activity (p = 0.000 and r = 0.449), family support (p = 0.000 and r = 0.607), and medication adherence (p = 0.000 and r = 0.726) with blood pressure .Conclusion: There is a significant relationship and the direction between the knowledge, attitude, diet, physical activity, family support, and medication adherence with blood pressure.